PENERAPAN PEMBELAJARAN NUMBERED HEADS TOGETHER BERBANTUAN MEDIA AUDIO UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK SISWA SEKOLAH DASAR - Januarni, Tri; Sabri, Tahmid; Kaswari, Kaswari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem ini this study is whether the application of the numbered heads together learning model assisted by audio media can improve the ability to listen to the fifth grade students of the Pontianak city public elementary school 03. This research uses descriptive method with class action research (PTK) and is collaborative. Subjects in this study were teachers as researchers and VB class students totaling 30 students. This research was carried out in even semester in Pontianak city state elementary school 03. This procedure is used in 4 stages, namely the planning stage, implementation phase, observation and reflection stages. The technique used is observation and scrutiny of documents with data collection tools are observation sheets and documents inspection sheets. The results of the research on students listening skills using numbered heads together learning model assisted by audio media in cycle 1 is 3 students who complete by obtaining an average score of 59.86. In cycle 2,15 students were completed by obtaining an average score of 77.56. in cycle 3, 27 students were completed by obtaining an average score of 82.13. it can be concluded that the application of the numbered heads together type learning model assisted by audio media can improve the ability to listen to the fifth grade students of the Pontianak city public elementay school 03. Keywords: Numbered Heads Together, Audio Media, Listening Skills